Technique for Order Preference by Similarity to Ideal Solution(TOPSIS) Untuk Penentuan Subsidi Listrik - Karlena Indriani; Sumanto Sumanto; Hariyanto Hariyanto; Ade Christian; Ruhul Amin; Lita Sari Marita (Sekolah Tinggi Teknik PLN, 2022)
Poverty is a condition where a person or household has insufficient income to meet the minimum living needs. BPS states that 40% of Indonesians are in the lowest economy. One of the measures to tackle poverty by the government is the application of electricity subsidies. The government in collaboration with PT. PLN to control poverty has an electricity subsidy program by providing electricity subsidy assistance funds to underprivileged communities. The purpose of the subsidy is to achieve electricity supply and help poor customers and those who have not been contacted by PT. PLN so that they can participate in enjoying electrical energy. However, there are still obstacles where there are many procedures so that it takes a long time to make decisions, because it must be seen from several criteria. One of the methods used to overcome the many criteria of FMADM is TOPSIS to complete 10 alternatives including: Job, Income, Dependents, Vehicle Assets, Home Ownership, Building Area, Drinking Water Source, Electrical Power Range, type of floor, and type of house wall. The results of the study obtained accurate results, namely from 20 submissions, only 11 residents were automatically acceded without having to wait a long time in the decision to grant electricity subsidies. And for 9 residents, they were given recommendations to be acc, 1 citizen was given a recommendation not to be acc